The Aesthetics of Antichrist : From Christian Drama to Christopher Marlowe - Parker, John, 1972- (Book collections on Project MUSE., 2007)
Crossing the divide between medieval and Renaissance theater while drawing heavily on New Testament scholarship, Patristics, and research into the apocrypha, this text proposes a wholesale rereading of pre-Shakespearean drama.